2014
DOI: 10.1039/c3gc42414f
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of fructose into 5-hydroxymethylfurfural catalyzed by recyclable sulfonic acid-functionalized metal–organic frameworks

Abstract: Sulfonic acid-functionalized metal–organic frameworks are efficiently used as recyclable solid acid catalysts for the fructose-to-HMF transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
204
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(227 citation statements)
references
References 47 publications
5
204
3
1
Order By: Relevance
“…7c), resulting in the activation energy and pre-exponential factor of 43.6 kJ·mol -1 and 1.4×10 6 h -1 . The calculated activation energy was much lower than that reported by ) in acetone-water catalyzed by ion exchange resin Dowex 50wx8-10 ( Qi et al 2008), and slightly lower than that reported by ) in DMSO catalyzed by sulfonic acid-functionalized metal-organic framework (Chen et al 2014), indicating that SBC catalyst can effectively lower the activation energy and lead to a higher reaction rate.…”
Section: Kinetic Studymentioning
confidence: 49%
See 1 more Smart Citation
“…7c), resulting in the activation energy and pre-exponential factor of 43.6 kJ·mol -1 and 1.4×10 6 h -1 . The calculated activation energy was much lower than that reported by ) in acetone-water catalyzed by ion exchange resin Dowex 50wx8-10 ( Qi et al 2008), and slightly lower than that reported by ) in DMSO catalyzed by sulfonic acid-functionalized metal-organic framework (Chen et al 2014), indicating that SBC catalyst can effectively lower the activation energy and lead to a higher reaction rate.…”
Section: Kinetic Studymentioning
confidence: 49%
“…According to ongoing studies, fructose dehydration to HMF obeys a pseudo-first order process (Chen et al 2014 …”
Section: Kinetic Studymentioning
confidence: 99%
“…Xu et al (2015a) also used the same catalyst in DMSO for HMF production with 79.6% HMF selectivity. Other catalysts such as FePO4 (Yang et al 2015b), Nb2O5 , graphite derivatives (Nie et al 2014), and sulfonic acidfunctionalized metal-organic frameworks MOF-SO3H (Chen et al 2014) have also been developed to produce HMF. In addition, a variety of biomass-derived carbonaceous solid acid materials have been demonstrated to be efficient for HMF production from fructose.…”
Section: Introductionmentioning
confidence: 99%
“…One is the filling of -SO 3 H groups in the pores that narrows the initially existing pores, in other words, the pore blockage contributes to the gradual disappearance of small pores. Another is the corrosion of the polymeric skeleton, especially in the presence of excessive chlorosulfonic acid, causing the decrease of mesopores [39]. An obvious evidence for the corrosion process is the formation of a large amount of macropores.…”
Section: Characterizationmentioning
confidence: 99%